The influence of Qur’anic ethics on responsible research for sustainable performance - Mhd. Sarif, Suhaimi (Zes Rokman Resources, 2018)
In recent years, responsible and accountable business researchers are highly sought after in the wake of Fourth Industrial Revolution due to deficit of trust and sustainability in the market. The automated and artificial intelligence driven connectedness and networking in the business world has serious deficiency in terms of trust, integrity, ethical and sustainable. The influence of Qur’anic ethics from Surah al-Mulk manifested a few ethical conducts necessary for business researchers in the Fourth Industrial Revolution. The study explored what are the factors influencing business researchers to have ethical conduct and responsible in all research projects. The study interviewed 10 technopreneurs in Malaysia to solicit their views on the factors influencing business researchers to behave ethically in conducting research. The feedback from the informants suggested three ethical factors namely the reason for existence into the strategic direction and purpose of enterprises, being vigilant in investment for any venture, and being consistent with character (khuluq) manifest the Qur’anic lessons from Surah al-Mulk for being ethical in conducting research so that the results of the research contribute to the performance of companies on sustainable manner. Keywords: Business researchers, Qur’an, Business Ethics.